Integrated Molecular, Interfacial, and Device Engineering towards High‐Performance Non‐Fullerene Based Organic Solar Cells. (18th June 2014) - Zang, Yue; Li, Chang‐Zhi; Chueh, Chu‐Chen; Williams, Spencer T.; Jiang, Wei; Wang, Zhao‐Hui; Yu, Jun‐Sheng; Jen, Alex K.‐Y.
<x xml:space="preserve">Abstract</x> High‐performance non‐fullerene OSCs with PCEs of up to ca. 6.0% are demonstrated based on PBDTT‐F‐TT polymer and a molecular di‐PBI acceptor through comprehensive molecular, interfacial, and device engineering. Impressive PCEs can also be retained in devices with relatively thick BHJ layer and processed through non‐halogenated solvents, indicating these high‐performance non‐fullerene OSCs are promising for large‐area printing applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>